Pain management within an enhanced recovery program after thoracic surgery - Thompson, Calvin; French, Daniel G.; Costache, Ioana (Journal of Thoracic Disease; Vol 10, Supplement 32 (November 20, 2018): Journal of Thoracic Disease (Enhanced Recovery: The Evidence Supporting Best Perioperative Care in Thoracic Surgery), 2018)
Evidence for ERAS within thoracic surgery (ERATS) is building. The key to enabling early recovery and ambulation is ensuring that postoperative pain is well controlled. Surgery on the chest is considered to be one of the most painful of surgical procedures for both open and minimally invasive surgery (MIS) approaches. Increasing use of MIS and improved perioperative care pathways has resulted in shorter length of stay (LOS), requiring patients to achieve optimal pain control earlier and meet discharge criteria sooner, sometimes on the same day as surgery. This requires optimizing pain control earlier in the postoperative recovery phase in order to enable ambulation and a better recovery profile, as well as to minimize the risk for development of chronic persistent postoperative pain (CPPP). This review will focus on the options for pain management protocols within an ERAS program for thoracic surgery patients (ERATS).